Adaptive tracking control of stochastic switched nonlinear systems with unknown dead‐zone output. (17th March 2021) - Liu, Yanli; Ma, Hongjun
Abstract: In this article, the problem of adaptive output feedback control is carried out for stochastic switched nonlinear systems with dead‐zone output and asymmetric tracking constraints. A type of smooth approximate model is proposed, which unfastens the nondifferentiable phenomena of dead‐zone output. The Nussbaum‐type function is utilized to develop the control design of the unknown dead‐zone output. Subsequently, an improved first‐order filter is cooperated into the barrier Lyapunov function analysis, which avoids the repeated derivative problem of virtual control inputs in the backstepping design procedure and completes the control design successfully. The proposed constructive control algorithm can achieve the control goal well. Finally, a numerical example with comparison results is given to further verify the validity of the new control tactic.